An Update on the Diagnosis, Treatment, and Management of Occipital Neuralgia. Issue 3 (9th May 2022) - Swanson, Daniel; Guedry, Ryan; Boudreaux, Megan; Muhlenhaupt, Emily; Kaye, Alan D.; Viswanath, Omar; Urits, Ivan
Abstract : Abstract: This report intends to summarize the underlying pathophysiology, relevant symptoms, appropriate diagnostic workup, necessary imaging, and medical and surgical treatments of occipital neuralgia (ON). This was done through a comprehensive literature review of peer-reviewed literature throughout the most relevant databases. The current understanding of ON is that it causes neuropathic pain in the distribution of the greater occipital nerve, the lesser occipital nerve, the third occipital nerve or a combination of the 3. It is currently a subset of headaches although there is some debate if ON should be its own condition. Occipital neuralgia causes chronic, sharp, stabbing pain in the upper neck, back of the head, and behind the ears that can radiate to the front of the head. Diagnosis is typically clinical and patients present with intermittent, painful episodes associated with the occipital region and the nerves described above. Most cases are unilateral pain, however bilateral pain can be present and the pain can radiate to the frontal region and face. Physical examination is the first step in management of this disease and patients may demonstrate tenderness over the greater occipital and lesser occipital nerves. Anesthetics like 1% to 2% lidocaine or 0.25% to 0.5% bupivacaine can be used to block these nerves and antiinflammatory drugs like corticosteroids can be used in combination to prevent compressive symptoms. Other treatments like botulinum toxin and radiofrequency ablation have shown promise and require more research. Surgical decompression through resection of the obliquus capitis inferior is the definitive treatment however there are significant risks associated with this procedure.